Uniform Water Potential Induced by Salt, Alkali, and Drought Stresses Has Different Impacts on the Seedling of Hordeum jubatum: From Growth, Photosynthesis, and Chlorophyll Fluorescence - Shi, Congcong; Yang, Fan; Liu, Zihao; Li, Yueming; Di, Xiaolin; Wang, Jinghong; Lin, Jixiang (Frontiers in Plant Science, 2021)
Hordeum jubatum is a halophyte ornamental plant wildly distributed in the Northeast of China, where the low water potential induced by various abiotic stresses is a major factor limiting plant growth and development. However, little is known about the comparative effects of salt, alkali, and drought stresses at uniform water potential on the plants. In the present study, the growth, gas exchange parameters, photosynthetic pigments, and chlorophyll fluorescence in the seedlings of H. jubatum under three low water potentials were measured. The results showed that the growth and photosynthetic parameters under these stresses were all decreased except for carotenoid (Car) with the increasing of stress concentration, and alkali stress caused the most damaging effects on the seedlings. The decreased net photosynthetic rate (Pn), stomatal conductance (Gs), and intercellular CO2 concentrations (Ci) values under salt stress were mainly attributed to stomatal factors, while non-stomatal factors were dominate under drought and alkali stresses. The reduced chlorophyll and slightly increased Car contents occurred under these stresses, and most significant changed under alkali stress. In addition, the maximum photochemical efficiency (Fv/Fm), actual photochemical efficiency (ΦPSII), and photochemical quenching coefficient (qP) under the stresses were all decreased, indicating that salt, alkali, and drought stresses all increased susceptibility of PSII to photoinhibition, reduced the photosynthetic activity by the declined absorption of light for photochemistry, and increased PSII active reaction centers. Moreover, the non-photochemical quenching coefficient (NPQ) of alkali stress was different from salt and drought stresses, showing that the high pH of alkali stress caused more damaging effects on the photoprotection mechanism depending on the xanthophyll cycle. The above results suggest that the H. jubatum has stronger tolerance of salt than drought and alkali stresses, and the negative effects of alkali stress on the growth and photosynthetic performance of this species was most serious.